2019
DOI: 10.1002/cbic.201800715
|View full text |Cite
|
Sign up to set email alerts
|

Ribosomal Peptides and Small Proteins on the Rise

Abstract: Genetically encoded and ribosomally synthesised peptides and small proteins act as important regulators in fundamental cellular processes, including gene expression, development, signalling and metabolism. Moreover, they also play a crucial role in eukaryotic and prokaryotic defence against microorganisms. Extremely diverse in size and structure, they are often subject to extensive post‐translational modification. Recent technological advances are now allowing the analysis of the whole cellular transcriptome a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 110 publications
0
17
0
Order By: Relevance
“…Many studies have shown that small proteins (≤100 amino acid residues) can be involved in important biological processes, including cell signaling, metabolism, and growth [21]. However, they are underrepresented in many genome annotations as they are notoriously hard to predict because of their small ORF size [21]. To validate these small peptides, we kept all ORF with at least 20 amino acids.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have shown that small proteins (≤100 amino acid residues) can be involved in important biological processes, including cell signaling, metabolism, and growth [21]. However, they are underrepresented in many genome annotations as they are notoriously hard to predict because of their small ORF size [21]. To validate these small peptides, we kept all ORF with at least 20 amino acids.…”
Section: Discussionmentioning
confidence: 99%
“…A compounding issue in emerging new fields is the development of a consensus on nomenclature [11]. As the underlying genes are denoted either as small or short ORFs, with both terms being used interchangeably, their gene products are hence named either small open reading frame encoded peptides (SEPs).…”
Section: Statement Of Significancementioning
confidence: 99%
“…The nomenclature and definition of the maximal size of the small proteins encoded by sORFs varies between 50 and 100 amino acids . Typically, peptides are distinguished from proteins by the shorter length of their chain.…”
Section: Introductionmentioning
confidence: 99%